METHODS OF DEFINING THE ANTHROPOGENIC TRANSFORMATION OF THE ENVIRONMENT - Berezhnoy, Vitaliy (Human Geography Journal, 2015)
The paper discusses some approaches to use the area ratios between different anthropogenic territorial complexes for assessments of environment state. The following definitions are considered: “natural-anthropogenic territorial complexes”, “antropization”. Some GIS-methods to calculate the antropization are suggested and results of such calculations at the example of key district are presented. The article raises the question of whether it is expedient to use basin approach while researching the environmental transformations. The attention is paid to the socio-economic context and the significance of such studies in human geography.